Upbringing as a Necessity and Freedom - Līdaka, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Upbringing is a purposeful process of internal and external conditions of life activity affected the process by which students develop and implement personally important attitudes towards themselves, other people, nature, culture, work, society and the state, acquiring the necessary competence for independent work. On the one hand, upbringing is a public necessity, on the other hand - the phenomen of personal freedom. That is the relationship between these two trends who can be discerned as personality driving force. Hence the importance of a deep understanding the upbringing as a necessity and freedom, which connects the targeted claims against the younger generation and its efforts to understand themselves, self-realization, to meet their growing needs, involving all forces, talents and abilities.